2013
DOI: 10.1590/s1677-5538.ibju.2013.03.16
|View full text |Cite
|
Sign up to set email alerts
|

Integration of collagen matrices into the urethra when implanted as onlay graft

Abstract: Objective: To assess the integration of decellularized heterologous collagen matrices into the urethra, when implanted with no cells or when seeded with autologous smooth muscle cells. Materials and Methods: Eighteen New Zealand rabbits were randomly assigned to two groups: Group I (n = 9) -animals undergoing urethral segment resection with interposition of a patch of heterologous collagen matrix seeded with autologous smooth muscle cells; Group II (n = 9) -animals undergoing resection of a urethral segment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…Therefore, two different slices were obtained to evaluate collagen fibers with Masson's trichrome staining in addition to HE staining in the present study. 31 Consistent with previous studies, our findings showed a significant increase in the number of collagen fibers in the tension area of all the appliance groups. Vitamin C has also been known to be directly related to collagen synthesis in previous experimental studies.…”
Section: Groupssupporting
confidence: 93%
“…Therefore, two different slices were obtained to evaluate collagen fibers with Masson's trichrome staining in addition to HE staining in the present study. 31 Consistent with previous studies, our findings showed a significant increase in the number of collagen fibers in the tension area of all the appliance groups. Vitamin C has also been known to be directly related to collagen synthesis in previous experimental studies.…”
Section: Groupssupporting
confidence: 93%
“…Normal inflammatory cell appearance was scored as zero; less than 25 % of all cells was scored as one; 25-50 % was scored as two and over 50 % was scored as three. 24 The epithelial integrity and structure and inflammation-related parameters were examined at 40× magnification. Fibrosis was determined from Masson´s trichrome-stained samples and scored.…”
Section: Histologymentioning
confidence: 99%
“…The pre-seeded matrix supported the reconstruction of a wide-caliber urethra without stricture, while the bare matrix failed (Orabi et al, 2013). Contrary to the previous study, the onlay application of bladder submucosa preseeded with autologous SMCs in rabbit did not demonstrate any significant regenerative advantage over the bare matrix, and both of them resulted in fully restored normal architecture of the urethra (Sayeg et al, 2013). In this regard, it has been shown that urine-derived stem cells cultured on SIS held superior capacity for regeneration of urethra.…”
Section: Urethral Tissue Engineeringmentioning
confidence: 57%
“…Similar to many organs treated by tissue engineering methods, collagen-based naturally derived scaffolds were among the first preferred options for reconstruction of urethra. This is because of the superior biocompatibility of these materials, and their supportive nature for cell attachment, growth, colonization, and remodeling of regenerating tissues (El-Tabey et al, 2012;Orabi et al, 2013;Sayeg et al, 2013;Wang et al, 2014;Liu et al, 2017). El-Tabey et al used a canine acellular bladder matrix, pre-seeded with autologous bladder cells (UCs and SMCs), for urethroplasty of 3 cm segment of the urethra in female dogs, and followed the regeneration process for 11 months.…”
Section: Urethral Tissue Engineeringmentioning
confidence: 99%